RESEPSI MASYARAKAT TERHADAP CERITA DATU SANGGUL (THE LEGEND OF DATU SANGGUL AS RECEIVED BY THE COMMUNITY) - Pifa Nuryani (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2021)
Abstract The legend of Datu Sanggul as received by the community. This research aims to describe the forms of reception and the factors causing the community (audience) to receive the Legend of Datu Sanggul. This is qualitative literary research through the receptive approach to literature. The data was collected through interviews, and field observations in the areas of the Datu Sanggul's Grave, and the documents of the manakib or books relating to the Datu Sanggul. The results of this research are (1) can be known the community's receptions on the Legend of Datu Sanggul are the forms of execution of annual commemoration of Datu Sanggul, the number of pilgrims to the Datu Sanggul's Grave, the habit of reciting manakib (biography), the presence of people who are eloquent in telling Datuk Sanggul's manakib, and the existence of the publication of manakib. (2) can be known the factors influencing the community to receive the Legend of Datu Sanggul are the factors of (a) the vows, wishful thinking/desires (positions, marriage partners, projects to build houses, etc), (b) the healing from illness, (c) the inner pressure and weak self-awareness based on which they hope they cured because of karomah of Datu Sanggul, (d) the socioculture, the family problem, the love towards a guardian. All factors and forms of community reception are influenced by community acceptance horizon factors such as background understanding of religion, religious emotions, social culture, and education. All the factors and forms of community's reception are influenced by the factors of the community's acceptance horizon such as the background of understanding of religion, religious emotions, social culture, and education. Key words: reception, legend, Datu SanggulAbstrak Resepsi Masyarakat Terhadap Cerita Datu Sanggul. Penelitian ini bertujuan untuk mendeskripsikan bentuk-bentuk resepsi dan faktor penyebab timbulnya tindakan resepsi masyarakat terhadap cerita Datu Sanggul. Penelitian ini berjenis penelitian kualitatif deskriptif melalui pendekatan resepsi sastra. Sumber data penelitian diambil dari tuturan informan baik melalui kegiatan wawancara, observasi lapangan di makam Datu Sanggul, dan dokumen manakib atau buku yang berkaitan dengan Datu Sanggul. Hasil dari penelitian ini adalah (1) dapat diketahui bentukbentuk resepsi masyarakat terhadap cerita Datu Sanggul berupa pelaksanaan haul Datu Sanggul tiap tahun, banyaknya peziarah ke makam Datu Sanggul, adanya kebiasaan membaca manakib, adanya orang yang fasih menceritakan riwayat Datu Sanggul, dan adanya buku manakib yang diterbitkan. (2) dapat diketahui faktorfaktor yang mempengaruhi tindakan resepsi masyarakat terhadap cerita Datu Sanggul adalah faktor adanya nazar, aktor adanya angan-angan/ keinginan (jabatan, jodoh, proyek membangun rumah, dsb.), faktor keinginan kesembuhan dari sakit, faktor tekanan batin dan kesadaran diri lemah sehingga berharap atau bertawassul melalui Datu Sanggul yang diyakini sebagai wali dan berkaromah, faktor sosial budaya, faktor masalah rumah tangga, dan faktor kecintaan terhadap wali. Semua faktor dan bentuk resepsi masyarakat tersebut dipengaruhi faktor horizon penerimaan masyarakat seperti latar belakang pemahaman keagamaan, emosi keagamaan, sosial budaya, dan pendidikan. Kata-kata kunci: resepsi masyarakat, cerita legenda, Datu Sanggul